Observation of the jet transition at a single vertical nozzle under pool scrubbing conditions. (15th June 2022) - Yoon, Jongwoong; Kim, Yo Han; Jeong, Yong Hoon
Highlights: Submerged air injection flow was visually observed from bubbly to jet flow regime. The local void fraction was measured at the center of the pool using an optical fiber probe. Bubbly to jet transition criteria was proposed based on the nominal Mach number conditions. The change of decontamination factor (DF) trend was identified at the jet transition criteria. Abstract: Submerged gas injection and the subsequent hydrodynamic behavior are phenomena that significantly affect the pool scrubbing efficiency at the injection zone. The Weber number jet transition criteria which have been normally used in the pool scrubbing research could not cover the wide range of the flow rate conditions including high-speed gas jet. In this study, the submerged air injection experiment was conducted at a 5 mm vertical nozzle. Air injection behavior was visually observed with a high-speed camera and analyzed using the shadowgraphy method. The local void fraction along the centerline of the pool was measured by using an optical fiber probe. From the measurement results, a jet transition criteria was suggested based on the nominal Mach number conditions. The effect of flow regime transition on the pool scrubbing efficiency has been confirmed through decontamination factor (DF) experiments. The suggested transition criteria matched with the DF experiment results.